SUPPLY MANAGEMENT IN THE SYSTEM OF CORPORATE SOCIAL RESPONSIBILITY (CSR) - Rustam Aslanzade (Economics & Education, 2018)
The article reveals the essence of such a sphere of entrepreneurial activity as Supply Management. In modern business, supply management is understood as a complex and integrated activity to generate all information about the company's in- and out-deliveries. An important aspect of supply management is the implementation of the concept of corporate social responsibility (CSR), which is an integral feature of modern civilized business. The implementation of CSR in the field of supply management is a very important direction for creating a positive image of any company.